2016
DOI: 10.1080/09712119.2016.1174127
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical changes of the seminiferous tubules and Leydig cells in Assam goats (Capra hircus) from birth to 10 months

Abstract: There is a definite pattern of the growth of seminiferous tubules at different post natal ages in mammals. The present work involves recording the changes of the seminiferous tubules, the cellular components of the seminiferous epithelium and the Leydig cells in male Assam goats. Different micrometrical parameters of the seminiferous tubules were found to increase with the increase in age of the male goats and they showed a significant (P < .05) increase between the age of 6 and 8 months. Also, the micrometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…The significant increase in diameter between 10 and 16 months indicated fast development of the tubules before sexual maturity. Similar findings were documented in Assam goats (Sarma and Devi, 2017) and cattle (Wrobel et al, 1988). Ibrahim et al (2013) reported that an increase in the process of spermatogenesis led to an increase in the thickness and diameter of seminiferous.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The significant increase in diameter between 10 and 16 months indicated fast development of the tubules before sexual maturity. Similar findings were documented in Assam goats (Sarma and Devi, 2017) and cattle (Wrobel et al, 1988). Ibrahim et al (2013) reported that an increase in the process of spermatogenesis led to an increase in the thickness and diameter of seminiferous.…”
Section: Discussionsupporting
confidence: 79%
“…The efficiency of Sertoli cells increased from 10 to 16 months of age in bulls. However, the present mean value for efficiency of Sertoli cell was relatively low when compared with other species such as Assam goats and gerbil (Segatelli et al, 2004;Sarma and Devi, 2017). The noticeable flexibility among species in the number of spermatids supported by a single Sertoli cell shows that, in general, species in which the ratio of spermatids to Sertoli cells is higher may also have a higher spermatogenic efficiency (Sharpe, 1984;França and Russell, 1998).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Scrotal circumference increases significantly between 12 and 18 months of age. Similarly, the results of [36] on Assam goats showed that the morphometry of seminiferous tubules and Leydig cells experienced a significant increase at the age of 6-8 months. Furthermore, according to [37] and [38] that the size of the scrotal circumference is influenced by body weight.…”
Section: Production Performancementioning
confidence: 74%
“…Follow-up results using the Duncan test showed that the seminiferous tubule diameter in the 12, 20 and 33 week age groups showed a significant difference (P <0.05). Sarma and Devi [25] stated that age has an effect on the increase in the diameter of the seminiferous tubules. a, b, c differences superscript within the same row indicate significant differences (P <0.05).…”
Section: Turkey Testicular Histomorphometrymentioning
confidence: 99%